Financial development as a product of capital accumulation. - Yermekova Yermekov, Zh. D. Zh. Zh. (Journal of Economic Research & Business Administration, 2016)
Under current conditions of different national economies are becoming increasingly interconnected and interdependent. The competitiveness of national economies depends on their ability to effectively and efficiently use internal financial resources and attract foreign investment on terms favorable to the country. Investing in innovation projects is a key element of sustainable economic development. Innovations are the driving force of development. The relationship between the financial and real sectors of the economy is an important factor of financial development. Countries are faced with constant growth of fictitious capital that does not create surplus value, reducing the value of money. Given the lack of financial resources in the post-Soviet economy there is an outflow of capital, which is in the form of «white», «gray», «black» capital. Multinational corporations are one example of an outflow of capital from the country, transferring profits to overseas parent companies.